Peran Keluarga Dalam Perawatan Jangka Panjang Lansia : Studi Kasus Di KP. Cicadas Kelurahan Pandeglang - Delia Ayunda Maulia; Alya Sabrina; Galuh Mulyawan (SELLAN : Jurnal Bimbingan dan Konseling, 2025)
Long-term care for the elderly is a critical issue that involves physical, emotional, and social aspects, often requiring significant support from the family. The family plays a vital role in providing continuous care, maintaining the elderly's well-being, and supporting their adaptation to aging-related changes. This study aims to explore the role of the family in the long-term care of an elderly person in Kp. Cicadas, Kelurahan Pandeglang, through a qualitative case study approach. Data were collected using in-depth interviews with the elderly and their caregivers. The findings reveal that family support, emotional bonding, and caregiving practices significantly influence the quality of life and psychological well-being of the elderly. Challenges such as caregiver burden, health limitations, and social isolation were also identified. The study concludes that strengthening family roles and providing adequate support to caregivers are essential to improve long-term care outcomes for the elderly. Keywords: elderly care, family role, long-term care, well-being